AN ANALYSIS OF TANSLATION QUALITY OF NOUN GROUP IN THE NOVEL THE BODY IN THE LIBRARY BY AGATHA CHRISTIE - Mahbub, Moh. Tarojjil; Sutrisno, Adi (Program Studi Bahasa Inggris, Universitas Panca Marga, 2023)
This research focuses on the Tanslation Quality of Noun Group in the Novel “The Body in the Library” by Agatha Christie to provide an explanation of the quality of the translation and find the noun groups contained in the novel. This research is important to do, because the quality of translations currently available cannot be measured for accuracy, so it can cause differences in the meaning that is conveyed from the source language to the target language. The theory used in this research is Halliday's systemic functional linguistic theory. The method used in this study is descriptive qualitative method. This method was chosen because we wanted to describe the quality of the translation in the noun group found in the novel The Body in the Library. the data in this study using the indirect observation and transcribing technique. indirect observationis done by reading novels. While note-taking technique is a data collection technique whose data source is written data. transcribing techniqueis used to write clauses containing noun groups in the novel the body in the library by Agatha Christie. This study uses the Spradley ethnographic method in analyzing the data Based on research conducted, The results of the noun group study are found 226 data and 11 contruction. D+T noun contruction 77 (34.07%) data. The next construction is D+C+T, 42 (18.58%) Data. The following are D+E+T and D+T+Q noun group contruction. Each of them is found 28 (12.23 %) Data. D+C+T+Q noun group contruction is found 15 (6.63%) data. The T+Q construction is found 9 data (3.93%). E+T construction is found 8 (3.53%) data. The D+E+C+T and D+E+T+Q noun group constructions have the same data. Each of the is 6 (2.65%) data. Furthermore, there are constructions D+E+C+T+Q and T+T which have only 1 (0.44%) data of each. Based on quality of noun group translation viewed from Systemic Functional Linguistics, 147 ( 83%) data are accurate. 79 (17%) data are not accurate.